Academic Stress and Burnout among Students in the Semester System: A Quantitative Investigation on Prevalence, Predictors, and Coping Strategies - Ania Shamim; Uzma Munawar; Hina Munir (Indus Journal of Social Sciences, 2025)
This research "Academic Stress and Burnout Among students in the Semester System: A Quantitative investigation on prevalence, predictors, and coping strategies" seeks to investigate the effects of academic stress on semester system learners and identify the strategies they use in coping with stress to avoid burnout. The primary aims are to explore the prevalence and causality of stress among semester system students, and determine the effective coping strategies practiced by students to overcome stress with the maintenance of academic achievement. A quantitative approach was used as the research design, and data were gathered using structured questionnaires from a sample of 250 BS and M.Phil Physics and Urdu department students of The Women University Multan and Emerson University Multan. The survey also inquired for the reasons of academic distress, such as workload; peer pressure, exam anxiety, and cost burden, and usage of coping strategies such as time management, social support, and relaxation skills by the students. Descriptive statistics and chi-square tests were used to examine the data. The findings showed high incidence of academic distress and burnout symptoms in students. Findings also suggested that students who used coping strategies effectively had less stress and greater academic engagement. Institution support and student-specific interventions are therefore vital in coping with academic stress as this study highlights. The study also underscores the importance of practicing healthy coping strategies to enhance students' psychological well-being and academic achievement in semester-based higher education systems.